THE IMPACT OF CONSUMING AMARANTHUS SPINOSUS L EXTRACT ON PROLACTIN LEVEL AND BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Okta Kuswaningrum; Agus Suwandono; Ida Ariyanti; Soeharyo Hadisaputro; Suhartono Suhartono (Belitung Raya Foundation, Indonesia, 2017)
Background: Breast milk is the best natural nutrient for the baby. However, some mothers have problems with breastfeeding due to lack of breast milk production. Spinach leaf (Amaranthus Spinosus L) is considered as one of the plants that have the effect of non-synthesis lactagogues to increase milk production. Objective: To analysis the effect of spinach leaf (Amaranthus Spinosus L) extract on prolactin and breast milk production in postpartum mothers. Methods: This was a quasi-experimental study with pretest posttest with control group design conducted in the Community Health Center of Wonogiri II Indonesia from December 2016 to January 2017. There were 30 participants were selected using purposive sampling, with 15 participants assigned in an experiment group and a control group. Data were analyzed using independent and paired t-test. Results: The results showed significant differences in prolactin levels (p = 0.000), breast milk production (p = 0.000), and infant weight (p = 0.000) (<0.05) after given spinach leaf (Amaranthus Spinosus L) extract. Conclusion: Spinach leaf (Amaranthus Spinosus L) extract had a significant effect in increasing the prolactin levels and breast milk production in postpartum mothers.